Development of Practical and Cost-Effective Ultra-High-Performance Engineered Cementitious Composites Using Natural Sand and No Silica Fume. Issue 7 (July 2022) - Game, Daniel; Arce, Gabriel; Hassan, Marwa M.; Noorvand, Hassan; Subedi, Sujata; Rupnow, Tyson
The objective of this study was to evaluate the feasibility of developing practical and cost-effective ultra-high-performance engineered cementitious composites (UHP-ECCs) using natural river sand and no silica fume (SF). Fresh and hardened properties of composites utilizing river sand, with and without SF, and incorporating 1.5 and 2 vol% (volume percent) ultra-high-molecular-weight polyethylene fibers were evaluated. Furthermore, matrix and fiber/matrix interface properties were investigated. Experimental results showed that the inclusion of SF generally produced negative impacts in the mechanical strength (i.e., compressive, tensile, and flexural) and ductility of the composites, which was mainly attributed to a worsening fiber dispersion. This was supported by the loss in workability observed when increasing fiber content or implementing SF. Clear tendencies in the effect of fiber content on the mechanical strength of the composites were not observed. However, increment in fiber content decreased the tensile ductility of the materials, presumably because of poor fiber dispersion. All the mixtures evaluated exhibited pseudo strain-hardening (PSH) behavior and ECC-like ductility, which was supported by the PSH strength and energy indexes obtained, which exceeded the minimum recommended values for robust PSH behavior. Practical and cost-effective UHP-ECC materials (i.e., cementitious composites simultaneously exhibiting compressive strength >120 MPa and tensile strain capacity >2%) using natural river sand and no SF were successfully developed, which to the authors' knowledge was achieved for the first time.